Mitigation of Carbonaceous Indoor Aerosols Through Behavioural Change Soft Approach in Cooking at Selected Rural Sites (India) - Kopal Verma; Umesh Chandra Kulshrestha (Aerosol and Air Quality Research)
Abstract Indoor air pollution particularly from biomass burning, presents a significant challenge in rural India. Despite awareness of cleaner energy sources, rural communities encounter financial and logistical barriers hindering their transition to cleaner energy. The combustion of biomass emits substantial amounts of carbonaceous aerosols (CA), including organic carbon (OC) and elemental carbon (EC), which severely impact health and contribute to climate change. This study is aimed at applying certain behavioural changes in cooking practices, termed here as ‘Soft Approaches,’ to mitigate indoor air pollution. Soft approaches involve minor adjustments in daily practices to promote sustainability. Conducted over a year at three sites in Punjab (Phullanwal) and Madhya Pradesh (Budhwada and Khedla), the study assessed CA concentrations in rural household kitchens. Outdoor CA concentrations were also measured in order to examine the indoor and outdoor differences in CA levels. Mostly, OC and EC concentrations peaked during the winter season, with outdoor levels consistently lower than indoor ones. The implementation of soft approaches such as using table fans for smoke dispersion, employing dried biomass, enhancing ventilation, utilizing biomass in pellet form resulted in reductions of up to 87.1% and 83.6% in indoor OC and EC concentrations, respectively. Questionnaire analysis indicated that the community recognized the benefits of cleaner fuels and soft approaches, despite challenges related to availability and economic feasibility. The adoption of soft approaches offers broader benefits by enhancing adaptive capabilities, fostering resilience to environmental challenges for individuals and the nation as a whole.